Adsorption and Desorption Properties of Beta Carotene in Crude Palm Oil on Activated Carbon Composites of Oil Palm Empty Fruit Bunches with MOFs-Cu(TAC) - Frengky Sanjaya Ginting; Yunita Dwi Utami; Desika Devani Br Surbakti; Dika Fahreza; Wella Apriwidyanti; Therecia Fricillia Ginting; Putri Faradilla; Rini Selly; Jasmidi; Moondra Zubir (Universitas Negeri Medan, 2025)
Oil palm bunches Empty fruit bunches are the main lignocellulosic solid waste that has not been optimally utilized, so many empty bunches are not processed. Unprocessed EFB causes a foul odor and becomes a place for flies to nest. Thus, it is considered as waste that pollutes the environment. Adsorption is a popular new method to reduce heavy metal content and waste in water, in addition the adsorption method is also effective and efficient in terms of the absorption process, and can also be a regeneration adsorbent. This study began with the preparation of empty oil palm bunches which were then carbonized and activated with H3PO4, then synthesized with MOFs-Cu(TAC). The final stage was tested for absorption by optimizing mass and time. The XRD pattern shows sharp peaks that appear on the graph indicating metal contact and the KA-Cu(TAC) composite has a good and regular crystal structure. The KA-Cu(TAC) composite has great potential as an alternative adsorbent to improve the quality of palm oil because it has good absorption.